FAKTOR-FAKTOR YANG MELATARBELAKANGI KETIDAKPATUHAN IBU HAMIL MEMERIKSAKAN KEHAMILAN KE TENAGA KESEHATAN DI WILAYAH PUSKESMAS SUNGAI SEMBILAN - Anurza, Septiana Dwi; ", Misrawati "; Hasanah, Oswati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The importance of antenatal care services regularly is to determine the health of the mother and fetus. In fact at Sungai Sembilan Health Center there are many pregnant women get antenatal care to the health worker. This study aims to determine the factors underlying the non-compliance of pregnant women in antenatal care to health workers in the area of Sungai Sembilan Health Center. Design of the study was descriptive correlation design. This research was conducted in Sungai Sembilan Health Center with 60 samples based on inclusion criteria using purposive sampling techniques. The instrument used in this study is a questionnaire. The univariate analysis was conducted to show frequencies and percentages and bivariate analysis was conducted by Chi-square test. The results showed that there was significant relation between parity factor (0.004) and the support of her husband (0.011), with noncompliance pregnant women in antenatal care and there is no relationship between the age factor (0.711), education (0.264), knowledge (0.188), attitude (0.726), geographic or distance of residence (0.650), and income (0.961), with the non-compliance of respondents in antenatal care. The results of this study can be a reference for health centers to improve the compliance of pregnant women antenatal so the quality of maternal health is to increasing.Keywords: pregnant mother, non-compliance, antenatal care